Pengaruh Komite Audit, Opini Audit, dan Financial Distress terhadap Audit Delay - Damayanti, Riska; Setyawan, Andri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to reveal the influence of the audit committee, audit opinion, and financial distress on audit delay. This type of research uses an associative quantitative research method. The population in this study are non-cyclical consumer companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2019–2024. The sampling technique in this study is based on purposive sampling technique. The population in this study is 95 companies listed on the Indonesia Stock Exchange in the infrastructure sector. With the sample selection criteria obtained a sample of 47 companies, so the number of data observations is 282. This study uses a statistical tool, namely eviews software version 12. The analysis technique used is logistic regression. The results show that partially the audit committee and audit opinion have no effect on audit delay, while financial distress does affect audit delay. And simultaneously the audit committee, audit opinion and financial distress affect audit delay.